Metabolic Disorders in Chronic Lung Diseases - Papaioannou, Ourania; Karampitsakos, Theodoros; Barbayianni, Ilianna; Chrysikos, Serafeim; Xylourgidis, Nikos; Tzilas, Vasilis; Bouros, Demosthenes; Aidinis, Vasilis; Tzouvelekis, Argyrios (Frontiers in Medicine, 2018)
Chronic lung diseases represent complex diseases with gradually increasing incidence, characterized by significant medical and financial burden for both patients and relatives. Their increasing incidence and complexity render a comprehensive, multidisciplinary and personalized approach critically important. This approach includes the assessment of comorbid conditions including metabolic dysfunctions. Several lines of evidence show that metabolic comorbidities including diabetes mellitus, dyslipidemia, osteoporosis, vitamin D deficiency and thyroid dysfunction have a significant impact on symptoms, quality of life, management, economic burden and disease mortality. Most recently, novel pathogenetic pathways and potential therapeutic targets have been identified through large-scale studies of metabolites, called metabolomics. This review article aims to summarize the current state of knowledge on the prevalence of metabolic comorbidities in chronic lung diseases, highlight their impact on disease clinical course, delineate mechanistic links and report future perspectives on the role of metabolites as disease modifiers and therapeutic targets.